2008
DOI: 10.1016/j.cellsig.2008.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Recycling of the human prostacyclin receptor is regulated through a direct interaction with Rab11a GTPase

Abstract: Running Title: Role of Rab11 and Rab4 in recycling of the human prostacyclin receptor.Key Words: human prostacyclin receptor, internalization, Rab11a, Rab4a, yeast-two-hybrid, GPCR. -2 - ABSTRACTThe human prostacyclin receptor (hIP) undergoes agonist-induced internalization but the mechanisms regulating its intracellular trafficking and/or recycling to the plasma membrane are poorly understood.Herein, we conducted a yeast-two-hybrid screen to identify proteins interacting with the carboxyl terminal (C)-tail do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 62 publications
(98 reference statements)
1
41
0
Order By: Relevance
“…We and others reported that an interaction between Rab proteins and GPCRs dictates the trafficking of the receptors (22)(23)(24)(25)(26)(27)(28)(29). However, whether other components of the Rab protein modification machinery or Rab effectors also interact with GPCRs remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We and others reported that an interaction between Rab proteins and GPCRs dictates the trafficking of the receptors (22)(23)(24)(25)(26)(27)(28)(29). However, whether other components of the Rab protein modification machinery or Rab effectors also interact with GPCRs remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Rab-mediated vesicular transport is well known to regulate membrane receptor trafficking, but less is known about whether membrane receptors conversely regulate the Rab-trafficking machinery. We and others showed that GPCRs interact with Rabs resulting in the regulation of receptor trafficking (22)(23)(24)(25)(26)(27)(28)(29). The task of unraveling whether membrane receptors interact with other elements of the Rab-associated machinery to direct their own trafficking remains.…”
Section: Previous Reports By Us and Others Demonstrated That G Proteimentioning
confidence: 99%
“…20 We and others established that a direct interaction between a GPCR and a Rab GTPase appears to be necessary in the proper trafficking of the receptor. 4,7,12,15,[17][18][19] Rab-mediated vesicular transport is well known to regulate membrane receptor trafficking, but less is understood about whether membrane receptors conversely regulate the Rab-trafficking machinery. [21][22][23] In this regard, an elegant study performed by Seachrist et al determined that activation of the angiotensin type 1 receptor stimulates the GTP-loading of Rab5a, suggesting that the receptor could act as a potential GEF or might recruit a GEF protein, thereby increasing the level of GTP-bound Rab5a.…”
Section: Gpcrs and The Regulation Of Rab Gtpasesmentioning
confidence: 99%
“…2 During the last decade, many studies described the involvement of Rab GTPases in the regulation of GPCR trafficking and signaling. Rab GTPases were shown to be key regulators of GPCR anterograde and retrograde transport (Rab1, Rab2, Rab6, and Rab8), [3][4][5][6] endocytosis (Rab5), [7][8][9][10][11] recycling (Rab4 and Rab11), [11][12][13][14][15][16][17][18][19] and degradation (Rab7). 20 We and others established that a direct interaction between a GPCR and a Rab GTPase appears to be necessary in the proper trafficking of the receptor.…”
Section: Gpcrs and The Regulation Of Rab Gtpasesmentioning
confidence: 99%
“…These interactions mediate diverse functions such as the regulation of T lymphocyte migration through interaction of the CCR5 and CXCR4 chemokine receptors with myosin heavy chain IIA [46] and the regulation of the recycling of the prostacyclin receptor through a direct interaction with Rab11a [47,48]. In many cases, the intracellular carboxyl-terminal (C) tail of the GPCR has emerged as the critical binding domain for such interactions with various GIPs, largely due to its divergent sequence, structure and capacity to contain functionally distinct binding motifs [44,45,49].…”
Section: Introductionmentioning
confidence: 99%